EVALUASI IMPLEMENTASI SERTIFIKASI HALAL TERHADAP PELAKU USAHA MIKRO DAN KECIL - Astika Yuliana, Rindi; Latif Pramana, Ratih; Adam Ghozali, Renando; Samca Susi, Kristina; Suradji Muhammad, Adji (CV. Lafadz Jaya, 2024)
Indonesia is one of the countries with the largest Muslim population in the world. As mandated by the 1945 Constitution, the government has an obligation to protect all its citizens, including providing halal food. The government has issued Government Regulation no. 33 of 2021 concerning the Implementation of Halal Product Guarantee and Regulation of the Minister of Religion No. 20 of 2021 concerning Halal Certification for Micro and Small Business Actors. This research aims to evaluate the implementation of these two regulations for MSEs. The method chosen in this research is a literature study with the hope of expanding the scope of information regarding the implementation of halal certification for food and beverages produced by MSEs. The research results show taret the halal certification program for food and beverages produced by MSEs is not yet fully effective and has not had a direct impact on improving the economy of MSEs. Currently, what MSEs need is how to create a market and also brand their business so that it has uniqueness.